Decision Support System for Poor Student Aid Recipients Using the Analytical Hierarchy Process (AHP) Method - Ratnawati, Heri; Iskandar, Akbar; Ahmed Abdulmajeed; Haryanto; Ridha Nur Ilahi (Ceddi Journal of Education, 2023)
The enforcement of mandatory education programs facilitates funding for primary and secondary schools, aligning with legal provisions designed to boost student engagement. Nevertheless, a stark reality persists, with numerous children unable to attend school, leading to dropouts and an inability to progress. A key factor contributing to this issue is the School Operational Assistance (BOS) not covering essential educational costs like uniforms, books, and shoes. The challenge lies in identifying suitable recipients for Poor Student Aid, hindered by insufficient categorized support data. Addressing this, a targeted solution involves designing a system, utilizing the Analysis Hierarchy Process (AHP) Method. Decisions regarding poor student aid approval would then be grounded in rational, objective considerations. Proactively implementing a structured decision support system is crucial in assigning significance to criteria values and weights, tailored to SD Negeri Baddoka Makassar's needs. Through AHP, the selection process becomes more transparent, measurable, and accountable. The resulting decisions have the potential to enhance the efficiency of providing assistance to those genuinely in need.